Konstruksi Indikator dan Formula Penilaian Kualitas Pemilu di Indonesia - Lati Praja Delmana; Aidinil Zetra; Alfan Miko (Universitas Medan Area, 2019)
General elections in Indonesia that have been carried out since 1955 have proceeded without having clear election quality indicators and indicators. Improving the quality of elections is one of the keys to realizing quality democracy. Standard indicators and evaluations of the quality of elections in previous studies were not able to represent the principles of Pancasila democratic values, local political cultural values, and heterogeneous conditions of Indonesian society, so special studies were needed to improve election quality standards in accordance with conditions in Indonesia. The purpose of this study is to develop indicators and instruments for assessing the quality of National Elections in Indonesia. The research method used is library research supported by the results of relevant research. Indicators for evaluating the quality of elections are built through all aspects of the pre, post and post-election governance process. All aspects meet the principles of equality, freedom, justice, transparency, professionalism, security, integrity and adjustment of local political culture. Assessment of election quality can be carried out through the opinion trail method and measured by ordinal measurement scale. Standardization The national election quality index established and developed in accordance with the times, guarantees the accuracy of measuring the quality of elections, so that the quality of elections can be improved on an ongoing and consistent basis.